Probe corrected near-field to far-field transformations from planar scanned near-field data - Morgan, D. A. G.(Derek Andrew Gwyn) (Stellenbosch : Stellenbosch University, 2012)
Study project (M. Ing.) -- University of Stellenbosch, 1989.